The effect of seeding rate and row spacing on seed yield and yield components of squarrosum clover and crimson clover in Southern Italy - Cazzato E.; Corleto A. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
A trial was conducted for two years (1989 and 1990) at Gaudiano di Lavello (41 degrees 06 minutes 00 seconds N; 15 degrees 51 minutes 09 seconds E; 145 m. a.s.l.) with the objective to test the effect of seeding rate (5 - 10 -15 -30 kg ha-1) and row spacing (20 - 40 - 60 cm) on seed production of squarrosum clover (two-year trial) and crimson clover (one- year trial: 1990). The year effect was very evident on seed yield and yield components (plants per m2, heads per m2, seeds per head) of squarrosum clover, mainly due to the difference in total rainfall (314 mm and 241 mm, respectively in 1989 and 1990) through the growing season (Nov. June), although in the second year 250 m3 per ha of irrigation water were applied at the end of March. The seeding rate of 10 kg ha-1 and the row spacing of 20 cm gave the highest seed yield in both species. However, the increase in row spacing strongly reduced the seed yield in crimson clover.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)